If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -4(-1x + -9) + 5 = -1(-5x + -4) + -2 Reorder the terms: -4(-9 + -1x) + 5 = -1(-5x + -4) + -2 (-9 * -4 + -1x * -4) + 5 = -1(-5x + -4) + -2 (36 + 4x) + 5 = -1(-5x + -4) + -2 Reorder the terms: 36 + 5 + 4x = -1(-5x + -4) + -2 Combine like terms: 36 + 5 = 41 41 + 4x = -1(-5x + -4) + -2 Reorder the terms: 41 + 4x = -1(-4 + -5x) + -2 41 + 4x = (-4 * -1 + -5x * -1) + -2 41 + 4x = (4 + 5x) + -2 Reorder the terms: 41 + 4x = 4 + -2 + 5x Combine like terms: 4 + -2 = 2 41 + 4x = 2 + 5x Solving 41 + 4x = 2 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. 41 + 4x + -5x = 2 + 5x + -5x Combine like terms: 4x + -5x = -1x 41 + -1x = 2 + 5x + -5x Combine like terms: 5x + -5x = 0 41 + -1x = 2 + 0 41 + -1x = 2 Add '-41' to each side of the equation. 41 + -41 + -1x = 2 + -41 Combine like terms: 41 + -41 = 0 0 + -1x = 2 + -41 -1x = 2 + -41 Combine like terms: 2 + -41 = -39 -1x = -39 Divide each side by '-1'. x = 39 Simplifying x = 39
| 0.06=0.04+y+0.04y | | 6x+12=8x+24 | | 6*2*3*2/(16/4) | | 12=3k-6k | | 3c-43=4C-64 | | 2+5s=2 | | 7(-3)2= | | 7s=s+96 | | f(12)=3x-3 | | 8k=5k | | -1x=23 | | x+7+2x+13=4x+2 | | 8k=5j | | F(12)=12 | | 76.8t-16t^2=0 | | 8x+3(x-6)=5(x+2)-5 | | t+11=2t | | 10y^2+27+5y=0 | | x+14+3x+4=5x+3 | | 9x+3y=393 | | 8x+3(x-6)=5(y+2)-5 | | 8-2x=3x-5 | | 20x-16=4x+3.5 | | 3n+9=4n | | 12x^2+3-12x=0 | | 23.8=3.5n | | y=16x^2+96x | | K^2-15k+50=0 | | 15(.3-z)+14.5z=2(.5z-10) | | 5x-14=33 | | -5a=6a-44 | | 320+80x=880 |